IBUPROFEN AS A MEDICATION FOR A CORRECTION OF SYMPTOMS OF NORMAL VACCINAL PROCESS IN CHILDREN - T.A. Chebotareva ("Paediatrician" Publishers LLC, 2008)
The pathogenetic approach to treatment of symptoms of normal vaccinal process in children after standard vaccination, based on the results of application of anti9inflammatory medications - ibuprofen (nurofen for children) and paracetamol is presented in this article. Clinical activity of ibuprofen was established on the basis of clinica catamnestic observation of 856 vaccinated children aged from 3 months to 3 years. recommendations for application of these medications as a treatment for a correction of vaccinal reactions are given. Key words: children, ibuprofen, paracetamol, vaccination.